2020
DOI: 10.1038/s41467-020-15267-z
|View full text |Cite
|
Sign up to set email alerts
|

Microglial metabolic flexibility supports immune surveillance of the brain parenchyma

Abstract: Microglia are highly motile cells that continuously monitor the brain environment and respond to damage-associated cues. While glucose is the main energy substrate used by neurons in the brain, the nutrients metabolized by microglia to support surveillance of the parenchyma remain unexplored. Here, we use fluorescence lifetime imaging of intracellular NAD(P)H and time-lapse two-photon imaging of microglial dynamics in vivo and in situ, to show unique aspects of the microglial metabolic signature in the brain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 115 publications
7
149
2
Order By: Relevance
“…Specifically, we detected an increase in intracellular m +2 13 C 2 -lactate in a glucose-dependent fashion, suggesting the possibility of an alternative metabolic pathway of BHB that is enhanced under glucose-limiting conditions. It has been reported that microglia cells have a flexible metabolism and in conditions of glucose deprivation can rapidly shift to use glutamine to sustain mitochondrial metabolism and surveillance functions [ 17 ]. Thus, to test the possibility that BHB could rescue microglia proliferation in conditions of very low glucose, we cultured BV2 and HMC3 cells in 0.1 mM glucose supplemented with 5 or 10 mM unlabelled BHB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we detected an increase in intracellular m +2 13 C 2 -lactate in a glucose-dependent fashion, suggesting the possibility of an alternative metabolic pathway of BHB that is enhanced under glucose-limiting conditions. It has been reported that microglia cells have a flexible metabolism and in conditions of glucose deprivation can rapidly shift to use glutamine to sustain mitochondrial metabolism and surveillance functions [ 17 ]. Thus, to test the possibility that BHB could rescue microglia proliferation in conditions of very low glucose, we cultured BV2 and HMC3 cells in 0.1 mM glucose supplemented with 5 or 10 mM unlabelled BHB.…”
Section: Resultsmentioning
confidence: 99%
“…In microglia, this phenomenon of the so-called metabolic flexibility and the utilisation of alternative substrates other that glucose is still poorly understood. Only very recently it has been reported that microglia can switch to utilise glutamine as an alternative fuel in the absence of glucose to support microglial function [ 17 , 18 ]. The matter of metabolic flexibility gains relevance as more evidence emerges regarding the significance of the metabolic microenvironment in regulating the immune function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their immune functions, microglia crucially support brain development, for example, by sculpting neuronal synapses in the developing brain. In the adult brain, microglia perform multiple functions, including monitoring changes in neuronal activity, modulating learning and memory, and acting as local phagocytes and damage sensors in the brain parenchyma (6)(7)(8)(9)(10)(11)(12).…”
Section: Microglia Are Central To Neuronal Function and Healthmentioning
confidence: 99%
“…Perhaps not surprisingly, the availability of a specific set of AA and their metabolism also have specific implications for the immune cell response in fascinating ways. Thus, the sensing of extra-and intracellular AA levels by mTOR and its purpose of controlling anabolic-catabolic balance is of prime importance to understand immunometabolism and its connection to AA [330]. Here, we will highlight some of the known functions of arginine, tryptophan, and glutamine concerning microglia immunometabolism.…”
Section: Amino Acid Metabolism and Immune Functions Of Mtormentioning
confidence: 99%
“…Glutamine may also serve as an alternative energy source supplying the TCA cycle/OxPhos as a precursor to α-ketoglutarate by actions of glutaminase (GLS) and glutamate dehydrogenase (GDH) in similar fashion as in glutamine-addicted cancer cells [349] with the goal of ensuring a well-functioning immune surveillance. Bernier and colleagues have demonstrated that glucose-deprived microglia displayed a high degree of metabolic flexibility in vivo and in vitro by utilizing a switching mechanism from glucose as energy source to glutaminolysis in an mTOR-dependent manner [330]. Glutamine as an immunometabolite demonstrates the flexibility of microglia to use alternative energy sources in order to execute their functions.…”
Section: Glutamine: the Alternative Energy Sourcementioning
confidence: 99%